A first insight into tuberculosis transmission at the border of Ecuador and Colombia: a retrospective study of the population structure of Mycobacterium tuberculosis in Esmeraldas province - Bernardo Castro-Rodriguez; Sebastián Espinoza-Andrade; Greta Franco-Sotomayor; Greta Franco-Sotomayor; José Manuel Benítez-Medina; Natalia Jiménez-Pizarro; Camilo Cárdenas-Franco; Juan Carlos Granda; Jose Luis Jouvin; Solon Alberto Orlando; Solon Alberto Orlando; Javier Hermoso de Mendoza; et al. (Frontiers Media S.A., 2024)
ObjectiveTuberculosis (TB) is a major public health concern in Ecuador and Colombia, considering that both countries are high-burden TB settings. Molecular epidemiology is crucial to understand the transmission dynamics of Mycobacterium tuberculosis complex (MTBC) and to identify active transmission clusters of regional importance.MethodsWe studied the potential transmission of TB between Colombia and Ecuador through the analysis of the population structure of MTBC lineages circulating in the Ecuadorian province of Esmeraldas at the border with Colombia. A total of 105 MTBC strains were characterized by 24-loci MIRU-VNTR and spoligotyping.ResultsMTBC lineage 4 is only present in Esmeraldas; no MTBC strains belonging to Lineage 2-sublineage Beijing were found despite its presence in other provinces of Ecuador and, in Colombia. Genotyping results revealed a high degree of diversity for MTBC in Esmeraldas: Neither active transmission clusters within this province nor including MTBC strains from Colombia or other provinces of Ecuador were found.ConclusionOur data suggest that tuberculosis dynamics in this rural and isolated area may be not related to highly transmitted strains but could be influenced by other health determinants that favor TB relapse such as poverty and poor health system access. Further studies including a larger number of MTBC strains from Esmeraldas are necessary to test this hypothesis.